Media Digital Dalam Pembelajaran Untuk Mendukung Keterampilan Abad 21 di SMP Plus Miftahul Falah Kuningan - Handayani Handayani; Ilah Nurlaelah; Ina Setiawati; Nanda Wildani; Diana Rahmah F (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This activity aims to enhance the knowledge of teachers at SMP Plus Miftahul Falah in utilizing digital media and AI-based applications to aid the learning process, develop teaching materials, create assessment tools, and design learning resources. The rapid advancement of digital learning media and AI-based applications underscores the importance for teachers to acquire knowledge about their usage. The utilization of this technology serves as support for 21st-century skills. The target beneficiaries of this community service are the teachers of SMP Plus Miftahul Falah. To achieve this objective, the community service method includes counseling, demonstrations, and training on the use of digital media in education. This activity encourages teachers to harness technology according to their needs to improve the quality of education while also developing 21st-century skills.